Causal relationships between gut microbiome and obstructive sleep apnea: a bi-directional Mendelian randomization - Liu, Liangfeng; He, Guanwen; Yu, Rong; Lin, Bingbang; Lin, Liangqing; Wei, Rifu; Zhu, Zhongshou; Xu, Yangbin (Frontiers in Microbiology, 2024)
Background: Previous studies have identified a clinical association between gut microbiota and Obstructive sleep apnea (OSA), but the potential causal relationship between the two has not been determined. Therefore, we aim to utilize Mendelian randomization (MR) to investigate the potential causal effects of gut microbiota on OSA and the impact of OSA on altering the composition of gut microbiota.: Bi-directional MR and replicated validation were utilized. Summary-level genetic data of gut microbiota were derived from the MiBioGen consortium and the Dutch Microbiome Project (DMP). Summary statistics of OSA were drawn from FinnGen Consortium and Million Veteran Program (MVP). Inverse-variance-weighted (IVW), weighted median, MR-Egger, Simple Mode, and Weighted Mode methods were used to evaluate the potential causal link between gut microbiota and OSA. Results: We identified potential causal associations between 23 gut microbiota and OSA. Among them, genus Eubacterium xylanophilum group (OR= 0.86; P = 0.00013), Bifidobacterium longum (OR= 0.90; P = 0.0090), Parabacteroides merdae (OR= 0.85; P = 0.00016) retained a strong negative association with OSA after the Bonferroni correction. Reverse MR analyses indicated that OSA was associated with 20 gut microbiota, among them, a strong inverse association between OSA and genus Anaerostipes (beta= -0.35; P = 0.00032) was identified after Bonferroni correction.Our study implicates the potential bi-directional causal effects of the gut microbiota on OSA, potentially providing new insights into the prevention and treatment of OSA through specific gut microbiota.